Leveraging Artificial Intelligence to Combat Corruption: Innovative Solutions for Transparent Governance - Hartanto, Budi; Ikhwan, Ahmad; Eko Hendro Pramono, Doni; Sukri, Hamdan; Fitria Purnomo, Rosyana (RISTEC : Research in Information Systems and Technology, 2024)
Abstract: Corruption is one of the major problems that harms both the country and society, with far-reaching impacts on the economy and social stability. To combat corrupt practices, Artificial Intelligence (AI) has emerged as a promising tool for detecting and preventing corruption. This article aims to explore how AI can be applied in this context by identifying its potential, challenges, and solutions that can be provided.In terms of detection, AI can analyze large datasets collected from various sources, such as financial transactions, procurement reports, and interactions between government officials. Machine learning algorithms can be used to identify suspicious or unusual patterns that may indicate corrupt practices. Additionally, AI can also be applied in prevention, such as developing automated surveillance systems that provide early warnings of potential irregularities.However, the use of AI in the fight against corruption faces challenges, including issues related to data security, algorithmic bias, and the need for clear regulations. This article concludes that, despite these challenges, AI holds significant potential in strengthening anti-corruption efforts, particularly when combined with appropriate policies. The implementation of AI can be a strategic step in creating more transparent and accountable governance.